Expression of the Phosphatase Ppef2 Controls Survival and Function of CD8+ Dendritic Cells - Zwick, Markus; Ulas, Thomas; Cho, Yi-Li; Ried, Christine; Grosse, Leonie; Simon, Charlotte; Bernhard, Caroline; Busch, Dirk H.; Schultze, Joachim L.; Buchholz, Veit R.; Stutte, Susanne; Brocker, Thomas (Frontiers in Immunology, 2019)
Apoptotic cell death of Dendritic cells (DCs) is critical for immune homeostasis. Although intrinsic mechanisms controlling DC death have not been fully characterized up to now, experimentally enforced inhibition of DC-death causes various autoimmune diseases in model systems. We have generated mice deficient for Protein Phosphatase with EF-Hands 2 (Ppef2), which is selectively expressed in CD8+ DCs, but not in other related DC subtypes such as tissue CD103+ DCs. Ppef2 is down-regulated rapidly upon maturation of DCs by toll-like receptor stimuli, but not upon triggering of CD40. Ppef2-deficient CD8+ DCs accumulate the pro-apoptotic Bcl-2-like protein 11 (Bim) and show increased apoptosis and reduced competitve repopulation capacities. Furthermore, Ppef2-/- CD8+ DCs have strongly diminished antigen presentation capacities in vivo, as CD8+ T cells primed by Ppef2-/- CD8+ DCs undergo reduced expansion. In conclusion, our data suggests that Ppef2 is crucial to support survival of immature CD8+ DCs, while Ppef2 down-regulation during DC-maturation limits T cell responses.